Constructing Multichannel Carbon Fibers as Freestanding Anodes for Potassium‐Ion Battery with High Capacity and Long Cycle Life - Xu, Ying; Yuan, Tao; Zhao, Yahui; Yao, Hongfei; Yang, Junhe; Zheng, Shiyou (Advanced materials interfaces, 2020)
Potassium‐ion battery (PIB) is a potential low‐cost energy storage technology owing to the abundant source and wide distribution of potassium element. However, the PIB usually suffers from poor cycling and rate performance induced by volume expansion and sluggish potassiation kinetics. Herein, multichannel carbon fibers (MCCFs) are rationally constructed as freestanding PIB anodes by electrospinning suitable ratio of poly(methyl methacrylate)/polyacrylonitrile with subsequent calcination treatment. The MCCF electrode shows a high reversible capacity/charge capacity of 420.1/304.2 mAh g−1 at current density of 50 mA g−1 and delivers a capacity of 110.9 mAh g−1 over 2000 cycles at a higher current density of 2000 mA g−1. The excellent electrochemical performance is attributed to the unique multichannels in amorphous MCCFs for buffering volume change and facilitating electrolyte infiltration, as well as high conductivity of N‐, O‐doping in MCCFs. This strategy of fabricating multifunctional electrode materials provides an effective approach to develop high‐performance materials for cost‐effective alkali‐ion batteries. The multichannel carbon fibers (MCCFs) as freestanding anodes for potassium‐ion batteries are rationally constructed by electrospinning suitable ratio of poly(methyl methacrylate)/polyacrylonitrile with subsequent heat treatment. The MCCF anodes present high reversible capacity and excellent long‐term cycling performance, which are attributed to the unique multichannel structure and high conductivity of MCCFs, as well as in situ N‐, O‐doping in MCCFs.